Propuesta de intervención psicopedagógica Leer y escribir en la Universidad para el procesamiento comprensivo lector en estudiantes de primer ciclo de la Carrera de Psicopedagogía de la Facultad de la Educación, el Arte y la Comunicación, 2024-2025. - Castillo Lima, Pamela Elizabeth (2025)
The objective of this research was to design a proposal for a psychopedagogical intervention in reading and writing at the university level to promote reading comprehension among first-year students of the Psychopedagogy program. The study was conducted using a quantitative, descriptive, and correlational approach, rather than a cross-sectional, experimental approach. A sample of three professors was employed, who were given a semi-structured questionnaire to gather information on the reading and writing strategies used in the teachinglearning process. The data obtained were processed using Excel. The results show that the most frequently used strategy for reading comprehension is summarizing, followed by highlighting and note-taking (66.7%). Furthermore, 33.3% of professors use graphic organizers such as concept maps, flowcharts, and attribute wheels. Regarding writing strategies, 66.7% prioritize guided selfcorrection and the use of citation and reference examples, while 33.3% opt for peer review and working with reliable sources. It is concluded that instructors employ teaching strategies that promote reading comprehension; however, the use of more complex tools is limited, suggesting the need to diversify teaching practices. The "Reading and Writing at the University" proposal seeks to strengthen reading and writing skills through workshops designed to foster autonomy, critical thinking, and students' ability to meet the academic demands of their professional training